THE USE OF THE WEIGHTED PRODUCT METHOD IN A FOOD CHOICE DECISION SUPPORT SYSTEM FOR PATIENTS WITH TYPE 2 DIABETES MELLITUS - Tikaridha Hardiani; Arizona Firdonsyah; Amalia Nur Afifah (Transmisi: Jurnal Ilmiah Teknik Elektro, 2022)
Diabetes Mellitus is a disease caused by a disturbance in the balance between glucose transport into cells, which is stored in the liver and released by the liver, resulting in an increase in blood glucose levels. Diabetes Mellitus is listed as the top 6 cause of death in the world, so it should receive more attention. A person with Diabetes Mellitus must be able to maintain a diet and can only consume foods that are low in glucose, so the need for food selection for people with Type 2 Diabetes Mellitus is a must. The method used in this research is the Weighted Product as a choice of the multi-criteria calculation method and the research of literature for data collection through previous research. The results of this research using the calculation of the Weighted Product method, resulting in a ranking with the highest value of 0.065 and being the best alternative, namely Steamed Cassava.